The Evolution of Contemporary Fine Art: From Traditional to Digital - Syafira, Yumni (Journal of Studies on Art, Culture and Society, 2025)
This article examines the evolutionary journey of contemporary fine art, from its traditional roots to its transformation in the digital age. Through a qualitative approach that includes literature studies, content analysis, and in-depth interviews with contemporary artists, this research identifies significant changes in techniques, media, and artistic concepts that have occurred with the times. Social, political, and technological changes have prompted artists to experiment with new media and innovative methods, which are drastically changing the fine arts landscape. In addition, this article highlights the challenges and opportunities faced by artists in the digital age, including issues of authenticity, copyright, and adaptation to technology. By exploring examples of artworks from different periods, this article provides comprehensive insights into the dynamics and future of contemporary fine art.